2012
DOI: 10.1093/eurheartj/ehs057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aliskiren treatment on endothelium-dependent vasodilation and aortic stiffness in essential hypertensive patients

Abstract: Aliskiren increased nitric oxide availability in the forearm resistance arterioles of EH, an effect probably determined by an antioxidant activity, which can also contribute to improved peripheral wave reflection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 34 publications
0
34
0
7
Order By: Relevance
“…98 Aliskiren, a novel direct renin inhibitor, has been recently studied in humans by Virdis in a comparative study against ramipril. 99 Aliskiren produced a significantly greater reduction in augmentation index and improved the vasodilatory response to acetylcholine, however blood pressure and pulse wave velocity reduction was the same in both groups. Dorresteijn et al also suggest that aliskiren may provide benefits in endothelial function in comparison to moxonidine or hydrochlorothiazide.…”
Section: The Renin-angiotensin-aldosterone Systemmentioning
confidence: 86%
“…98 Aliskiren, a novel direct renin inhibitor, has been recently studied in humans by Virdis in a comparative study against ramipril. 99 Aliskiren produced a significantly greater reduction in augmentation index and improved the vasodilatory response to acetylcholine, however blood pressure and pulse wave velocity reduction was the same in both groups. Dorresteijn et al also suggest that aliskiren may provide benefits in endothelial function in comparison to moxonidine or hydrochlorothiazide.…”
Section: The Renin-angiotensin-aldosterone Systemmentioning
confidence: 86%
“…Direct Treatment of PWV A number of short-term randomised controlled trials investigating the blockade/ inhibition of renin [71], angiotensin converting enzyme/ angiotensin AT1 receptor blockers [72][73][74][75][76][77][78][79][80], endothelin [81], aldosterone [82,83], phosphodiesterase V [84,85], HMGcoA reductase [86][87][88][89][90][91][92] and xanthine oxidase [93] have been shown to reduce aortic PWV. An important randomised trial in patients with early renal impairment showed both PWV and left ventricular mass reduction over 1 year on just 25 mg spironolactone versus placebo, which the authors claimed was independent of BP [94].…”
Section: Origins Of Arterial Stiffness and Nurture Versus Nature?mentioning
confidence: 99%
“…19 These findings were found in hypertensive patients when BP was significantly reduced. On the other hand, valsatran reduced PWV when administered in hypertensive patients with albuminuria.…”
Section: Discussionmentioning
confidence: 91%